Identification and characterization by LC‐UV‐MS/MS of melanotan II skin‐tanning products sold illegally on the Internet. Issue 2 (25th April 2014) - Breindahl, Torben; Evans‐Brown, Michael; Hindersson, Peter; McVeigh, Jim; Bellis, Mark; Stensballe, Allan; Kimergård, Andreas
<x xml:space="preserve">Abstract</x> New methods were developed and validated to determine the identity, contents, and purity of samples of melanotan II, a synthetic melanocortin receptor agonist, sold in vials as injectable skin‐tanning products that were purchased from three online shops. Methods were based on liquid chromatography with ultra‐violet detection (LC‐UV) at wavelength 218 nm, and tandem mass spectrometric detection (MS/MS) after collision‐induced fragmentation of the double charged [M+2H]2+ precursor ion (m/z 513). Identification of melanotan II was verified by correct chromatographic retention time, and relative abundance ratios of five qualifying fragment ions. LC‐UV was used to quantify melanotan II as well as impurities. Method validation was performed with reference to guidelines for assessing active substances in authorized medicinal products to reach acceptable accuracy and precision. Vials from two shops contained unknown impurities ranging from 4.1 to 5.9%; impurities from one shop were below the quantification limit. The total amount of melanotan II in vials ranged between 4.32 and 8.84 mg, although each shop claimed that vials contained 10 mg melanotan II. A broad range of drugs used for enhancement purposes can be obtained from the illicit market. However, users of these drugs may be exposed to a range of potential harms, as shown in this study, given that these products are manufactured, distributed and supplied from an illicit market. Copyright © 2014 John Wiley & Sons, Ltd.